Pengaruh Suhu Terhadap Penyerapan Air Dan Kelarutan Resin Komposit - Kholidina Imanda Harahap; Rusfian Rusfian; Affan Ali Al-Harits (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
The existence of composite resin as dental restorative materials in the mouth will always be exposed to temperature changes from food or drink. The purpose of this study was to evaluate the effect of temperature on water absorption and solubility of the composite resin. Thirty samples made from nanofiller composite resin with a diameter of 15 mm and a thickness of 1 mm. The samples were divided into three test groups (n=10) that is immersed at 50 (I), 37 (II) and 5 °C (III). The testing procedure of water sorption and solubility of the composite resin made according to the ISO 4049: 2000 specifications. Data will be analyzed by one-way ANOVA and Least Significance Data test (p=0,05). The results showed there is significant differences of the water sorption (p=0,045) and solubility (p=0,018). The highest water sorption is group I (0,0057±0,007µg/mm3) than group II (0,0028±0,0013 µg/mm) and group III (0,0005±0,0006 µg/mm). While the heighest solubility values are in group I (0,003 ± 0,0027 µg/ mm), than group II (0,002 ± 0,0013 µg/mm) and group III (0,001 ± 0,00 µg/mm). It can be concluded that temperature could increase water sorption and solubility of composite resin.